PEMBINAAN KESADARAN LINGKUNGAN HIDUP DI PONDOK PESANTREN: STUDI KASUS DI PONDOK PESANTREN AL-MANSUR DARUNNAJAH 3 KABUPATEN SERANG - Ali Muhtarom (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2014)
This paper discusses the Islamic boarding school respond toward environmental problem and the implementation of Islamic values in environmental awareness development in Al-Mansur Darunnajah 3 Kabupaten Serang, Banten Islamic boarding school. There are three efforts; first, there is an enthusiasm on doing the religious teaching; second, proactive on doing the cleaning; and third, the school concern on developing the eco-Islamic boarding school. There are three kinds of Islamic values implementation; first, intrinstic concern on practising Islamic values; second, creating slogans about prohibition on any kind of environmental damage and throwing rubish, and popularize the motto â€œbersih, indah, dan amanâ€. The third, there are special rules conducting the environmental problems by giving punishment and organize the schedule for cleaning.